High Serum Asprosin Levels Are Associated with Presence of Metabolic Syndrome - Tao Hong; Jiao-Yang Li; Ya-Di Wang; Xiao-Yan Qi; Zhe-Zhen Liao; Poonam Bhadel; Li Ran; Jing Yang; Bin Yan; Jiang-Hua Liu; Xin-Hua Xiao (International Journal of Endocrinology)
Objective. Asprosin, a new adipocytokine, has reportedly been associated with glucose release, dyslipidemia, and insulin resistance (IR). However, the relationship of asprosin with metabolic syndrome (MetS) remains unknown. This study aimed to investigate serum asprosin levels in MetS as well as their association with various metabolic parameters in humans. Methods. A total of 131 consecutive patients with MetS, and 162 age-matched, healthy subjects were recruited for this study. Serum asprosin concentrations were determined using the enzyme-linked immunosorbent assay. Lipid profile, glucose, insulin, and inflammatory markers were also measured. Results. Serum asprosin levels were higher in subjects with MetS (23.52 [16.70, 32.05] ng/mL) than in controls (16.70 [12.87, 22.38] ng/mL; P<0.01), and they showed an increasing trend with increasing numbers of metabolic components (P for trend < 0.01). In all studied subjects, serum asprosin levels were positively correlated with body mass index, waist circumference, triglycerides, fasting plasma glucose, 2-hour plasma glucose, fasting insulin, homeostatic model assessment of insulin resistance (HOMA-IR) index, interleukin-6, and monocyte chemoattractant protein-1 and negatively correlated with high-density lipoprotein cholesterol (P<0.05). In multiple linear regression, asprosin was independently and positively correlated with triglyceride and HOMA-IR (P<0.05). Binary logistic regression revealed that asprosin was independently and positively correlated with the occurrence of MetS and IR, even after controlling for anthropometric variables, lipid profiles, and inflammatory markers. Conclusion. Asprosin is a potential metabolic-related adipokine and may be related to IR and MetS. This trial was registered with ChiCTR, ChiCTR1800018347.